Tunable porosity through cooperative diffusion in amulticomponent porous molecular crystal - Manurung,R; Holden,D; Miklitz,M; Chen,L; Hasell,T; Chong,SY; Haranczyk,M; Cooper,AI; Jelfs,KE (Journal of Physical Chemistry C, 2015)
A combination of different molecular simulation techniques was used to begin to uncover the mechanism behind the compositional tuning of gas sorption behaviour in a multicomponent porous molecular crystal, CC1.CC3n.CC41-n, where 0 < n < 1. Gas access to formally occluded voids was found to be allowed through a cooperative diffusion mechanism that requires the presence of the guest for the channel to briefly open. Molecular dynamics simulations and dynamic void analysis suggest two putative diffusion mechanisms. We propose that the gas diffusion is controlled by the cage vertices that surround the void, with the slightly smaller and more mobile cyclopentane vertices in CC4 allowing more facile nitrogen diffusion than the cyclohexane vertices in CC3. A combination of sorption simulations, void analysis and statistical calculations suggest the diffusion mechanism may rely upon the presence of two CC4 molecules adjacent to the occluded voids.